A Fractional Factorial Design to Study the Effect of Process Variables on the Preparation of Hyaluronidase Loaded PLGA Nanoparticles. (9th December 2014) - Narayanan, K.; Subrahmanyam, V. M.; Venkata Rao, J.
Abstract : The present study was initiated to understand the effect of PLGA concentration, PVA concentration, internal-external phase ratio, homogenization speed, and homogenization time on mean particle size, zeta potential, and percentage drug encapsulation using fractional factorial design. Using PLGA (50-50) as the carrier, hyaluronidase loaded PLGA nanoparticles were prepared using double emulsion solvent evaporation technique. The particle size was analyzed by dynamic light scattering technique and protein content by Lowry method. The study showed that homogenization speed as an independent variable had maximum effect on particle size and zeta potential. Internal-external phase volume ratio had maximum effect on drug encapsulation. Mean particle size also had high dependency on the combined effect of PVA concentration and phase volume ratio. Using fractional factorial design particle size of <400 nm, zeta potential of <−30 mV, and percentage encapsulation of 15–18% were achieved.